(untitled) (Research, Society and Development, 2021)
Tropical trees planting resurgent in a global warming scenario, and this activity relies on information about forest species ecology and its different functional traits. we evaluated the initial performance of Mimosa scabrella using the Generalized Linear Models (GLM) technique to fit mathematical models for collar diameter growth x height, and for crown projection area x collar diameter in a forest restoration planting. The following variables were obtained in the first four years after planting: collar diameter (mm), total height (m), crown projection area (m²) and crown volume (m³). The models fitting was performed by GLM on Gamma, Normal and Poisson distribution, identity and logarithmical join function, and they were analyzed based on Akaike and Bayesian Information Criteria, standard deviation of the estimate and determination coefficient. M. scabrella showed an excelled performance on the 48 months of age, with average increment of 200.28 mm in collar diameter, 6.88 m in total height, 2.95 m² in crown projection area and 83.41 m³ in crown volume. Its growth reduced only on periods of frost occurrence, but it restarted after these climatic events. The species growth, as well as its high survival rates and resprouting, allow its recommendation as a shady species of fast canopy fulfillment in forest restoration projects.